Identification of Indicators for Desertification - Mosmas, C; Tsara, M; Moustakas, N; Karavitis, Ch (Annals of Arid Zone, 2016)
Desertification is the consequence of a series of important degradation processes in semi-arid and arid regions, where water is the main limiting factor of land use performance on ecosystems. Environmental indicators can facilitate the assessment and monitoring of desertification by providing synthetic information on the status and trends of environmental processes leading to desertification. This paper analayses the importance of using indicators for defining areas vulnerable to desertification and the criteria for selecting indicators of desertification risk. Simple indicators related to the physical environment such as soil depth, slope gradient, slope exposure. parent material. rock fragment content, annual rainfall. aridity index, type of vegetation, plant cover. etc., and land management characteristics such as tillage operations, tillage depth, controlled grazing, period of exiting land use type, erosion control measures, etc., can be easily used for defining desertification risk. However, the use of indicators related to socio-economic characteristics of an area such as family size, farmer age, farm size, farmer income, land tenure, etc., should be treated very cautiously. analyzed at local conditions, and not generalized for other areas. The indicators become more effective when they are applied on the basis of land use type.